Sekularisasi dan Sekularisme Agama - Raden Datoek A. Pachoer (UIN Sunan Gunung Djati Bandung, 2016)
The Starting from the 19Th centuries, the word of secularization appears, the secularization is intended to hand over power and property rights to the state church and secular foundations. And in the 20th century, the term has developed a conceptual long, so it has meaning and significance vary. While in Indonesia the word secularization or secularism is the word 'proscribed' was to talked. In Indonesia the issue of secularization first raised in the 1970s by Nurcholish Majid and reap the pros and contra. Differences of secularization and secularism, secularization is understood as the process of release of Life is no longer dominated by the religious institution or authority of religious institutions. Secularization is also be interpreted as a separation movement or extrication themselves from the power of religious institutions in its various aspects. While secularism is as an ideology or ideologies that deny the existence of a sacred setting. The leaders agreed to the secularization and secularism modernization of Auguste Comte, for example, he announced that as a result of modernization, the people is grow beyond the